Movement at warp speed: technology and global markets are about to reshape America's metropolitan landscapes. - Suro, Roberto (American Demographics, 2000)
The U.S. economic landscape is increasingly being shaped by the movement of New Economy workers and the development of technology work centers. Metropolitan areas with technology-intensive employment have experienced a much faster rate of economic growth over the last 20 years than the U.S. as a whole. Moreover, the growth of high-tech industries in these areas has resulted in an influx of low-skilled, low-wage immigrants to provide various services for the technology workers. This kind of migration can have a huge impact on politics, culture, and economics, and it is crucial that businesses do not rest on their old assumptions relating to where people live in the U.S.